Beyond misinformation: developing a public health prevention framework for managing information ecosystems - Atsuyoshi Ishizumi, MPH; Jessica Kolis, MPH; Neetu Abad, PhD; Dimitri Prybylski, PhD; Kathryn A Brookmeyer, PhD; Christopher Voegeli, PhD; Claire Wardle, PhD; Howard Chiou, MD (Elsevier, 2024)
Summary: The COVID-19 pandemic has highlighted how infodemics (defined as an overabundance of information, including misinformation and disinformation) pose a threat to public health and could hinder individuals from making informed health decisions. Although public health authorities and other stakeholders have implemented measures for managing infodemics, existing frameworks for infodemic management have been primarily focused on responding to acute health emergencies rather than integrated in routine service delivery. We review the evidence and propose a framework for infodemic management that encompasses upstream strategies and provides guidance on identifying different interventions, informed by the four levels of prevention in public health: primary, secondary, tertiary, and primordial prevention. On the basis of a narrative review of 54 documents (peer-reviewed and grey literature published from 1961 to 2023), we present examples of interventions that belong to each level of prevention. Adopting this framework requires proactive prevention and response through managing information ecosystems, beyond reacting to misinformation or disinformation.